Examination of Cognitive Function, Neurotrophin Concentrations, and both Brain and Systemic Inflammatory Markers Following a Simulated Game of American Football. Issue 3 (26th March 2022) - Hoffman, Jay R.; Ostfeld, Ishay; Zamir, Amit; Amedi, Roee; Fonville, Tate R.; Horstemeyer, Mark F.; Gepner, Yftach
Abstract: Hoffman, JR, Ostfeld, I, Zamir, A, Amedi, R, Fonville, TR, Horstemeyer, MF, and Gepner, Y. Examination of cognitive function, neurotrophin concentrations, and both brain and systemic inflammatory markers following a simulated game of American football. J Strength Cond Res 36(3): 686–694, 2022—This investigation examined the effect of a simulated American football game on cognitive function, neurotrophin concentrations, and markers of both systemic and brain inflammation. Members of the Israel national team (6 linemen and 9 skill position players) were examined 1 week before (PRE), immediately post (IP) and 24-hour post (24P) game. Blood was obtained, and cognitive function was measured at each assessment. No head injuries to any of the players participating in the study occurred. Significant ( p < 0.001) decreases in acute memory, and a trend ( p = 0.066) toward a decrease in delayed memory was noted at IP. Significant negative correlations were observed between playing time (number of plays) and concentration changes from PRE to IP ( r = −0.801; p = 0.001) and from PRE to 24P ( r = −0.549; p = 0.034). All cognitive function measures returned to PRE levels by 24P. Increases from PRE were noted in tumor necrosis factor-alpha (TNF-α) ( p = 0.041) at IP and in brain-derived neurotrophic factor ( p = 0.009) and C-reactive protein (CRP) ( p = 0.019) concentrations at 24P. Circulating CRP concentrations and the cytokine markers, interleukin (IL)-4, IL-6, IL-10, and TNF-α, were significantly elevated in linemen compared with skill players. Brain inflammatory markers (S100B and glial fibrillary acidic protein) and total tau protein (a marker of brain injury) were not elevated from PRE. No change from PRE was noted in either myoglobin or creatine kinase-MM concentrations. In conclusion, muscle damage and inflammatory marker responses observed from the scrimmage game were consistent with muscle desensitization associated with football participation. In addition, the systemic inflammatory marker results observed in linemen were suggestive of chronic low-grade inflammation.